2007
DOI: 10.1002/bdrc.20101
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clocks during embryonic and fetal development

Abstract: Circadian rhythmicity is a fundamental characteristic of organisms, which helps ensure that vital functions occur in an appropriate and precise temporal sequence and in accordance with cyclic environmental changes. Living beings are endowed with a system of biological clocks that measure time on a 24-hr basis, termed the circadian timing system. In mammals, the system is organized as a master clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus, commanding peripheral clocks located in almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
88
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 107 publications
(120 reference statements)
3
88
0
5
Order By: Relevance
“…Previous studies have suggested that the fetus in the uterus uses maternal signals to adapt the fetal biological clock to the maternal environment (Reppert and Schwartz 1983;Davis and Gorski 1988;Parraguez et al 1996;Kennaway 2002;Ohta et al 2002Ohta et al , 2003Ohta et al , 2008Sládek et al 2004;Li and Davis 2005;Saxena et al 2007). These signals are considered to be a variety of nonphotic stimuli including circadian fluctuations in hormonal and nutritional signals from the mother, placental filtering of those signals, and uterine motility (Serón-Ferré et al 2007). The present study further supports this idea particularly by first proving the existence of stable circadian clocks in the pregnant uterus and the decidua at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have suggested that the fetus in the uterus uses maternal signals to adapt the fetal biological clock to the maternal environment (Reppert and Schwartz 1983;Davis and Gorski 1988;Parraguez et al 1996;Kennaway 2002;Ohta et al 2002Ohta et al , 2003Ohta et al , 2008Sládek et al 2004;Li and Davis 2005;Saxena et al 2007). These signals are considered to be a variety of nonphotic stimuli including circadian fluctuations in hormonal and nutritional signals from the mother, placental filtering of those signals, and uterine motility (Serón-Ferré et al 2007). The present study further supports this idea particularly by first proving the existence of stable circadian clocks in the pregnant uterus and the decidua at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Among them the suprachiasmatic nuclei (SCN) of the anterior hypothalamus function as the master pacemaker at the top of the hierarchy, and coordinate clocks in peripheral organs such as the heart, lung, liver, kidney, pancreas and non-pregnant uterus (Hastings et al 2003;Dolatshad et al 2006;Maywood et al 2007). During pregnancy, the fetus itself functions as an organ oscillator in the mother and uses maternal signals to adjust the fetal biological clock to the extrauterine environment (Serón-Ferré et al 2007;Ohta et al 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Diurnal rhythms in fetal HR and HRV are well established in late gestation in the fetal human (44), nonhuman primates (39), and sheep (3,4,9,11,42). These circadian rhythms are thought to be entrained by maternal signals (28) and coordinated, in part, by signals from a fetal "biological clock" in the suprachiasmatic nucleus (SCN) (5,26,41), although other fetal tissues may be involved (37). A study in infants and children showed a circadian rhythm in HR and HRV and confirmed progressive maturation of the autonomic nervous system with age, suggesting the hypothesis that the sympathetic withdrawal associated with mature, organized sleep is largely responsible for those rhythms (24).…”
mentioning
confidence: 99%